The Effect of Aging on AC-BC Asphalt Mixture with Molasses as a Substitute for Asphalt - Fadilah, Linda Winarni (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
Asphalt aging is one of the causes of quality deterioration in flexible pavement. Previous studies have shown that molasses can be used as a substitute for asphalt. This study uses molasses at 15% of the asphalt weight. Aging tests were conducted on AC-BC asphalt mixtures, which are intermediate layers often used in areas with high deformations. Asphalt aging occurs in both short and long terms. Short-term aging occurs during mixing, tested using Short-Term Oven Aging (STOA), while long-term aging occurs during service life, tested using Long-Term Oven Aging (LTOA). STOA testing involves heating the loose mixture in a laboratory oven for 4 hours at 135°C, while LTOA involves heating solid specimens in a laboratory oven for 2 days and 5 days at 85°C. The test results indicate that aging affects the characteristics of asphalt mixtures, as evidenced by an increase in Void in Mixture (VIM) and Void in Mineral Aggregate (VMA) values, while stability, flow, Void Filled with Bitumen (VFB), and density values tend to decrease. The test results also show that HMA AC-BC +15% Molasses is better at maintaining stability values, as evidenced by the higher stability value of HMA AC-BC + 15% Molasses compared to HMA AC-BC Control.